ANALISIS KELAYAKAN USAHA PRODUK HASIL HUTAN BUKAN KAYU (HHBK) GULA AREN: STUDI KASUS KELOMOK TANI SABAR MENANTI LOMBOK TIMUR - Hidayat, Lalu; Soimin, Muhamad (Jurnal Silva Samalas, 2021)
Sugar palm (Arenga pinnata merr), one of the tropical plants with important ecological and economic functions, produce various valuable non timber forest products in form of palm sugar, sap, fiber, flour, and leaves. A group of farmers run a business of palm sugar production in which the raw materials are collected from the forest. This study aimed to determine the business income of palm sugar and to evaluate the feasibility of palm sugar business that is run by the indigenous farmer community in Pringga Jurang Utara East Lombok. This study is descriptive explorative research with cencus data collection method, accommodating 20 farmers as respondents. The results show that the income of palm sugar business in a month is approximately of Rp. 374.894 and the feasibility score of palm sugar business is 2 â‰¥ 1 , indicating that each expenditure of Rp. 1 of the business generate the revenue of Rp. 2.